2013
DOI: 10.3390/ph6091094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology of Furosemide in Neonates: A Review

Abstract: Furosemide is the diuretic most used in newborn infants. It blocks the Na+-K+-2Cl− symporter in the thick ascending limb of the loop of Henle increasing urinary excretion of Na+ and Cl−. This article aimed to review the published data on the clinical pharmacology of furosemide in neonates to provide a critical, comprehensive, authoritative and, updated survey on the metabolism, pharmacokinetics, pharmacodynamics and side-effects of furosemide in neonates. The bibliographic search was performed using PubMed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 134 publications
(266 reference statements)
2
36
0
1
Order By: Relevance
“…The outcome of the NEMO trial is unfortunate but is in line with already available observations on furosemide related hearing impairments [6]. While the aforementioned mechanism has only been reported recently, the epidemiological data between loop diuretics and hearing impairment have been reported decades ago, using much lower doses of bumetanide.…”
Section: A Mechanism To Explain Ototoxicity In Neonatessupporting
confidence: 74%
“…The outcome of the NEMO trial is unfortunate but is in line with already available observations on furosemide related hearing impairments [6]. While the aforementioned mechanism has only been reported recently, the epidemiological data between loop diuretics and hearing impairment have been reported decades ago, using much lower doses of bumetanide.…”
Section: A Mechanism To Explain Ototoxicity In Neonatessupporting
confidence: 74%
“…Among factors that can mitigate this risk, the short-term administration of drugs with nephrotoxic potential, such as aminoglycosides and diuretics, is recognized [25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Mirochnick et al reported an average oral bioavailability of 84% when furosemide is delivered to children of 39 weeks gestational age. Whether this higher bioavailability originates from higher intestinal paracellular permeability remains to be confirmed as other explanations cannot be excluded .…”
Section: Age‐mediated Changes In Physiological Processes Determining mentioning
confidence: 98%